Sindhi Indigenous Ecological Knowledge: Sustainable Practices for Climate Change Resilience (Journal of Asian Development Studies, 2024)
The Sindhi people, who are indigenous to the Sindh region, have a rich tradition of Indigenous Ecological Knowledge (IEK) that has been developed and refined over centuries. The study has been designed to investigate the extent to which these conventional knowledge systems and practices foster sustainability and resilience in their respective communities in the face of climate change. This research emphasizes the efficacy of Sindhi IEK in adapting to and mitigating the effects of climate change by inspecting a variety of indigenous practices, including water management, agricultural techniques, natural resource conservation, and community governance. The practical outcomes of these practices are evaluated through a qualitative approach that incorporates semistructured interviews from N=10 experienced persosns with key community stakeholders which have extensive knowledge from the region of Village Baseero Tehsil FaizGanj District Khairpur, who are aged between 40 to 70 years. The results indicate that the integration of Sindhi IEK into more comprehensive climate adaptation strategies can provide valuable insights for sustainable development and resilience-building, particularly in regions that are confronted with comparable ecological challenges. This study emphasizes the necessity of preserving and reviving indigenous knowledge systems as essential instruments for fighting global climate change.